DIRASATU ASSULUKIYAH 'AN THARIQATI TA'ALLUMI AN NAHWI WA AS SHARFI - Sy, Azisi; Az, Nurfaiza (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2023)
Language is the most important social phenomenon in life and every social progress is mastered thanks to language. One of them is Arabic. Learning Arabic cannot be separated from the words of grammar and morphology. The study of grammar and morphology requires an applied method because the most important factor in the development of education, especially in the middle religious school Nour al-Huda, is the application of the learning style. Various efforts were made by the religious school and Professor Noor Al-Huda girls in teaching students who excel in religious knowledge. In addition, in the religious and middle school Nur al-Huda, he also teaches students to memorize and learn the sciences written by previous scholars, i.e. the inheritance book, with the aim that students are familiar with a clear foundation. In the study of the science of the book inheritance must deepen the science of grammar and morphology. Traditionalism in the world of education is closely linked, especially in the formation of students' behavior. With this theory, it has a great impact on learning, especially in learning grammar. The purpose of this study is to identify the methods, theories and materials applied in the middle religious school Nour al-Huda girls and to identify the positive and negative effects of the study of grammar and morphology. Data collected in this study